تطبيق طريقة القواعد والترجمة لترقية مهارة القراءة لدى طلاب المعهد الخاص دار القرآن والحديث - Ahmad Rijalullah; Dedy Wahyudin; Suparmanto Suparmanto (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2022)
This research was motivated by the researcher’s intention to know the application of qawaid and tarjamah method in improving reading skills, because the researchers see that the priority subjects are memorizing the qur’an & hadits. The aims of the researcher in the study are to find out : (1) Are the qawaid & tarjamah methods still applied in Special Darul Qur’an & Hadits Boarding School, although the priority is memorizing the qur’an & hadits. (2) What are the problems in the application of the qawaid & tarjamah method in improving students’ reading skills at the Special Islamic Boarding School Darul Qur’an & Hadits.